ARCH and GARCH Models on the Indonesian Sharia Stock Index - Budiandru Budiandru (Jurnal Akuntansi dan Keuangan Islam, 2021)
Investments in Islamic stocks are in demand because of the profit-sharing system so that the company is more stable in facing uncertain global economic conditions. This study aims to analyze the volatility of the Indonesian Sharia Stock Index and the Indonesian Sharia Stock Index's potential in the future. We use daily data from 2012 to 2020 and the Autoregressive Conditionally Heteroscedasticity-Generalized Autoregressive Conditional Heteroskedasticity (ARCH-GARCH) method. The results show that the Indonesian Sharia Stock Index's volatility is influenced by the risk of the two previous periods and the return volatility in the previous period. Potential Indonesian Sharia Stock Index tends to fluctuate in return by an average of 3 percent.Investasi pada saham syariah diminati karena sistem bagi hasilnya sehingga perusahaan lebih stabil dalam menghadapi kondisi ekonomi global yang tidak menentu. Penelitian ini bertujuan untuk menganalisis volatilitas Indeks Saham Syariah Indonesia dan potensi Indeks Saham Syariah Indonesia di masa yang akan datang. Kami menggunakan data harian dari 2012 hingga 2020, dan metode Autoregressive Conditionally Heteroscedasticity-Generalized Autoregressive Conditional Heteroskedasticity (ARCH-GARCH). Hasil penelitian menunjukkan bahwa volatilitas Indeks Saham Syariah Indonesia dipengaruhi oleh risiko dua periode sebelumnya dan volatilitas return pada periode sebelumnya. Potensi Indeks Saham Syariah Indonesia cenderung mengalami fluktuasi return dengan rata-rata sebesar 3 persen.